What Do We Know about Young Volunteers? An Exploratory Study of Participation in Zooniverse. (13th January 2020) - Herodotou, Christothea; Aristeidou, Maria; Miller, Grant; Ballard, Heidi; Robinson, Lucy
Citizen Science (CS) is an increasingly popular activity enacted either in the field or online. Volunteers participate in research activities such as data processing and analysis by, for example, identifying plants and animals. In this paper we examine young people's participation in online CS projects hosted on the Zooniverse platform. This is an exploratory study, the first of its kind that focuses on young people, mainly 16–19 years old. It uses data analytics and visualisation techniques to capture participation in online CS, and in particular to answer the following questions: (a) What does young people's participation look like in CS projects? (b) What Zooniverse projects do young people choose to participate in? and (3) What Zooniverse projects do young people choose together? Findings revealed five distinct engagement profiles characterising young people's participation and identified certain projects as been more popular across participants. Implications for the design of online citizen science projects targeting young people are discussed.